Application of SQC and ANOVA in Quality Control of Palm Kernel Oil - Wilda Roeska Simatupang; Nos Sutrisno; Haniza, Haniza; Ninny Siregar; Budhi Santri Kesuma; Reakha Zulvatricia (Universitas Medan Area, 2024)
The measurement and control of free fatty acids (FFA), moisture content (MC), and impurity content (IC) using Statistical Quality Control (SQC) in the oil production process were crucial to ensure optimal quality of palm kernel oil (PKO). This study aimed to determine the variance influencing the quality of PKO using Anova analysis. Anova (Analysis of Variance) is a statistical test procedure used to test mean differences among more than two groups. The results of the study indicated that the analysis of variance Fcount values for free fatty acids, moisture content, and impurity content were smaller than the Ftable values, indicating that the measurement results or mean values of these four data groups did not have statistically significant differences.